1993
DOI: 10.1159/000129290
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Evaluation of Wound Healing of Rabbit Oviduct after Microsurgical Reanastomosis with the Use of Autologous Fibrin Adhesive, Human Fibrin Adhesive or Poly-Glycolic Acid Suture

Abstract: The morphology of the healing process of microsurgical re-anastomosis of the rabbit oviduct with the use of fibrin adhesive, autologous and heterologous, and conventional sutures is described. Both oviducts in 48 rabbits were cut and reanastomoses were performed. The rabbits were killed at different intervals after the operations, ranging from 2 h to 28 days, and the anastomoses were evaluated by histomorphological examination.The autologous fibrin adhesive was absorbed after a week and an uncomplicated healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This implies that the adhe sion of the sealant for the tissue is the decisive factor for gluing tissue [10]. Autologous fibrin glue is completely resorbed after several days by fibrinolysis and induces a minimum of tis sue reactions [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the adhe sion of the sealant for the tissue is the decisive factor for gluing tissue [10]. Autologous fibrin glue is completely resorbed after several days by fibrinolysis and induces a minimum of tis sue reactions [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods of preparing fibrin glue from the patients' own plasma or from single donor plasma have been described. The methods are based on the separation of fibrinogen by cryoprecipitation, by precipitation with ammoni um sulfate, polyethylene glycol, ethanol, or the use of a whole plasma fibrin gel [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This has not been the case in studies on rabbits where differences were found after sealing of their oviducts with hu man or autologous rabbit glue. The human glue caused a granulomatous inflammation which was interpreted as an immune reaction to the foreign protein, whereas the autologous glue resulted in uncomplicated healing [11], In summary, we found that air leak after experimental lung surgery was reduced signif icantly by the use of fibrin glue made from plasma by ethanol precipitation. The glue ap peared to be biocompatible and to function as a scaffold for cell growth.…”
Section: Discussionmentioning
confidence: 63%
“…Re ecting the 1943 ndings of Tarlov et al [38,39] regarding autologus plasma clots, more recent studies suggest that AFG obviates possible immunologic responses to non-AFG and consequently acclerates healing [31,46,[81][82][83]. Many methods of autologous brinogen have been described with varied bonding strengths [21,59,74,75,78,84].…”
Section: Fibrinogen Precipitation/ Autologous Fibrin Gluementioning
confidence: 99%
“…Many methods of autologous brinogen have been described with varied bonding strengths [21,59,74,75,78,84]. Although AFG adhesive strengths are generally inferior to those of commercial products, they are suf cent for many of the attempted surgerical procedures [21,24,59,[83][84][85][86]. Most hematology laboratories can prepare AFG quickly and economically on the same day of surgery and even intraoperatively [79,84].…”
Section: Fibrinogen Precipitation/ Autologous Fibrin Gluementioning
confidence: 99%